2015
DOI: 10.18805/ijar.7081
|View full text |Cite
|
Sign up to set email alerts
|

Single nucleotide polymorphisms in Heat Shock Protein (HSP) 90AA1 gene and their association with heat tolerance traits in Sahiwal cows

Abstract: Heat Shock Proteins (HSPs) are group of proteins which are synthesized during heat stress. HSP genes have been reported to be associated with heat tolerance and production performance in cattle. HSP90AA1 gene has been mapped on Bos taurus autosome 21 (BTA 21) and spans nearly 5368 bp comprising 11 exons out of which first exon does not translate. The present study was carried out in Sahiwal cows (n=100) with the objectives to identify SNPs in targeted regions (exon 3, 7, 8 & 11) of HSP90AA1 gene and to analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…The respiration rate is a reliable physiological parameter for predicting heat stress in dairy cattle (Dalcin et al, 2016) and increases with THI. Published literature also revealed higher respiration rates in cattle during summer, when THI values increase (Kumar et al, 2015;Sailo et al, 2015a;Verma et al, 2015 andDas, 2014). The increase in respiration rate in summer as compared to other seasons may be due to the more demand for oxygen by the tissues in stressful conditions.…”
Section: Respiration Rate (Rr)mentioning
confidence: 92%
See 2 more Smart Citations
“…The respiration rate is a reliable physiological parameter for predicting heat stress in dairy cattle (Dalcin et al, 2016) and increases with THI. Published literature also revealed higher respiration rates in cattle during summer, when THI values increase (Kumar et al, 2015;Sailo et al, 2015a;Verma et al, 2015 andDas, 2014). The increase in respiration rate in summer as compared to other seasons may be due to the more demand for oxygen by the tissues in stressful conditions.…”
Section: Respiration Rate (Rr)mentioning
confidence: 92%
“…58 ± 0.38, 25.94 ± 0.38 and 21.90 ± 0.38 in summer, rainy and winter seasons respectively. Several authors (Kumar et al, 2015;Sailo et al, 2015a;Verma et al, 2015 andDas, 2014) also reported higher respiration rates of Sahiwal cattle and (Deb et al, 2013;Sailo et al, 2015b;Verma et al, 2015 andDas, 2014) in HF crossbred cattle during summer as compared to winter season. Increased respiration is an important physiological response, which aids in dissipation of excess body heat by vaporizing more moisture in the expired air (Atkins et al, 2018).…”
Section: Respiration Rate (Rr)mentioning
confidence: 95%
See 1 more Smart Citation
“…HSP90AA1 belongs to the group of heat shock proteins (HSPs) which play a vital role in protecting cells from environmental stress. Kumar et al ( 113 ) conducted a study in Sahiwal cows to identify SNPs in exons 3, 7, 8, and 11 of HSP90AA1 and study its association with thermal tolerance. They reported a total of five SNPs (A1209G, A3292C, T4935C, T5218C, and A5224C) in this breed of indigenous cattle, among which two, A1209G and A3292C, had a significant association with heat tolerance traits.…”
Section: Biomarkers For Identifying Thermo-tolerant Dairy Cowmentioning
confidence: 99%
“…The most common and temperature-sensitive is HSP90, which is thought to play an important role in environmental stress and thermal adaptation (Gade et al, 2010;Aritonang et al, 2017;Puteri et al, 2018). In summer, higher levels of expression of proteins of the HSP70 and HSP90 families have been observed in a variety of livestock species (Archana et al, tolerance, milk production, fertility, and disease susceptibility in livestock (Shergojry et al, 2014a;Kumar et al, 2015;Bhat et al, 2016). They may be useful as candidate gene markers for identifying animals with enhanced climatic resistance, immunological response, and performance (Hassan et al, 2019).…”
Section: Introductionmentioning
confidence: 99%